Quantification of the Adhesion Strength of Candida albicans to Tooth Enamel - Gubesh Gunaratnam (MDPI AG, 2021)
Caries is one of the most prevalent diseases worldwide, which is caused by the degradation of the tooth enamel surface. In earlier research the opportunistic pathogen Candida albicans has been associated with the formation of caries in children. Colonization of teeth by C. albicans starts with the initial adhesion of individual yeast cells to the tooth enamel surface. In this study, we visualized the initial colonization of C. albicans yeast cells on pellicle-covered enamel by scanning electron microscopy. To quantitatively unravel the initial adhesion strength, we applied fluidic force microscopy-based single-cell force spectroscopy to examine the key adhesion parameters adhesion force, rupture length and de-adhesion work. We analyzed single saliva-treated or untreated yeast cells on tooth enamel specimens with or without salivary pellicle. Under all tested conditions, adhesion forces in the lower nanonewton range were determined. Furthermore, we have found that all adhesion parameters were enhanced on the pellicle-covered compared to the uncovered enamel. Our data suggest that initial adhesion occurs through a strong interaction between yeast cell wall-associated adhesins and the salivary pellicle. Future SCFS studies may show whether specific management of the salivary pellicle reduces the adhesion of C. albicans on teeth and thus contributes to caries prophylaxis.